2013
DOI: 10.4172/2329-6895.1000117
|View full text |Cite
|
Sign up to set email alerts
|

Motor Neurons Exhibit Sustained Loss of Atrophy Reversal in Immunodeficent Mice

Abstract: Our lab showed previously that whereas a substantial portion of chronically resected facial motor neurons reside in an atrophied state that can be reversed at 14 days following reinjury in wild-type (WT) mice, atrophy reversal was altered in immunodeficient mice. It was unclear, however, if the abnormal response at day 14 post-reinjury in immunodeficient mice might be due to differences in the kinetics of the reversal response or impaired regeneration. We sought to address this question, and test our working h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Reinjuring the facial nerve stimulates a reversal in the atrophic status of the injured neurons, causing an increase in both their size and number [7]. As described below, data from our research suggests that under normal physiological conditions, the reversal of atrophy and the ability of reinjured facial motor neurons to regain their normal phenotype is dependent on a normal functioning cellular immune system [8,9]. To our knowledge, this is the only model of neuronal atrophy reversal that has been studied in the context of immunity or linked to immune function.…”
Section: Atrophied Neurons Have the Potential To Regenerate Their Phementioning
confidence: 99%
See 4 more Smart Citations
“…Reinjuring the facial nerve stimulates a reversal in the atrophic status of the injured neurons, causing an increase in both their size and number [7]. As described below, data from our research suggests that under normal physiological conditions, the reversal of atrophy and the ability of reinjured facial motor neurons to regain their normal phenotype is dependent on a normal functioning cellular immune system [8,9]. To our knowledge, this is the only model of neuronal atrophy reversal that has been studied in the context of immunity or linked to immune function.…”
Section: Atrophied Neurons Have the Potential To Regenerate Their Phementioning
confidence: 99%
“…This study was designed to test our hypothesis that the normal regeneration of atrophied motor neurons is dependent on normal adaptive immunity, and to determine if there were differences in kinetics of the reversal response between the groups. We compared motor neuron survival and size between WT and RAG2-KO mice in the facial nerve reinjury paradigm at 3 and 28 days post-reinjury [9]. Our results showed that in WT mice, facial motor neurons that were resected for 10 weeks and subsequently reinjured were able to regain fully an apparent 40% loss of countable neurons at 3 days post-reinjury, and nearly half of the magnitude of that that robust increase in neurons was sustained at 28 days post-reinjury.…”
Section: Chronic Axotomy Of Facial Motor Neurons T Cells and Atrophymentioning
confidence: 99%
See 3 more Smart Citations